2015
DOI: 10.1016/j.ijggc.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic and global sensitivity analyses of uncertain parameters affecting the safety of geological carbon storage in saline aquifers of the Michigan Basin

Abstract: Geological carbon storage (GCS) has been proposed as a favorable technology to reduce carbon dioxide (CO 2 ) emissions to the atmosphere. One of the main concerns about GCS is the risk of CO 2 escape from the storage formation through leakage pathways in the sealing layer. This study aims at understanding the main sources of uncertainty affecting the upward migration of CO 2 through preexisting "passive" wells and the risk of fissuring of target formation during GCS operations, which may create pathways for CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In recently, Baù et al . proposed an iterative global pressure solution (IGPS) for the semi‐analytical solution of Nordbotten and Celia, and González‐Nicolás et al . discussed the stochastic and sensitivity of the residual saturation of brine by using the iterative global pressure solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recently, Baù et al . proposed an iterative global pressure solution (IGPS) for the semi‐analytical solution of Nordbotten and Celia, and González‐Nicolás et al . discussed the stochastic and sensitivity of the residual saturation of brine by using the iterative global pressure solution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult for engineers to understand and apply. In recently, Baù et al 37 proposed an iterative global pressure solution (IGPS) for the semi-analytical solution of Nordbotten and Celia, and González-Nicolás et al 38 discussed the stochastic and sensitivity of the residual saturation of brine by using the iterative global pressure solution. However, the iterative global pressure solution is a numerical arithmetic whose results rely on numerical iteration, which introduced the problem of accuracy, convergence and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical algorithms using several assumptions can quickly obtain storage capacity. These analytical algorithms include those for multiphase flow, semi-analytical algorithms of multiphase (two-phase) flow, solute-transport models of multiple phases and multiple species, coupled multiphasereaction-temperature algorithms, coupled geomechanics-flow algorithms, and others (Claridge, 1972;Nordbotten et al, 2005;Okwen et al, 2010;Szulczewski et al, 2014;González-Nicolás et al, 2015;Ganjdanesh and Hosseini, 2018;Middleton et al, 2020;De Simone and Krevor, 2021). The analytical algorithms are preferred because they require a relatively small amount of data based on the idealized or conceptual model and can provide quick assessments with acceptable resolutions, especially for basin or sub-basin scale evaluations with limited data.…”
Section: Analytical Algorithmsmentioning
confidence: 99%
“…This finding is consistent with the results of stochastic simulations of multiphase flow. The importance of the permeability of the injection formation in application to geological CO 2 storage was pointed out in González et al (2015). Authors found that the aquifer permeability have a significant influence on the pore pressure producing a wide-spread range of fluid overpressure in their stochastic analysis.…”
Section: Pore Pressure Responsesmentioning
confidence: 99%